KONTEN VISUAL INSTAGRAM SEBAGAI UPAYA BRANDING DESA WISATA SAAT PANDEMI COVID-19: Studi Kasus pada Instagram Desa Kemiren, Desa Penglipuran dan Desa Waerebo - Hanindharputri, Made Arini; Ariesta, I Gusti Bagus Bayu Baruna; Utami, Sri (Institut Bisnis dan Teknologi Indonesia, 2022)
The COVID-19 pandemic that has lasted since 2020 has had a major impact on the tourism sector. This uncertain situation has made various countries produce policies for traveling both at home and abroad. World tourism, including Indonesia, needs time to return to being able to generate visitors. Various efforts and strategies have been made to save Indonesian tourism. One of them is by doing branding including branding on tourist villages on social media, namely through presenting visual content on Instagram. The choice of tourist village in this study is because Indonesia has villages with natural, cultural and traditional potential, community communities to culinary diversity. The research method used is a qualitative descriptive method with case studies from several tourism village Instagram accounts that have potential and are analyzed based on branding variables. It was found that the selection of the right visual content such as showing the identity of the tourist village and testimonials became effective content for branding the tourist village. In addition, the consistency of visual elements is also an important factor in improving the image of a tourist village. This study aims to determine effective visual content in branding for tourist villages so that it is expected to revive the tourism sector and the creative economy in Indonesia since the Covid-19 pandemic.